Clinical Trials in Thrombosis: Secondary Prevention of Myocardial Infarction - Klimt, Christian R; Doub, P. H; Doub, Nancy H (Thrombosis and Haemostasis, 1976)
Numerous in vivo and in vitro experiments, investigating the inhibition of platelet aggregation and the prevention of experimentally-induced thrombosis, suggest that anti-platelet drugs, such as aspirin or the combination of aspirin and dipyridamole or sulfinpyrazone, may be effective anti-thrombotic agents in man. Since 1971, seven randomized prospective trials and two case-control studies have been referenced in the literature or are currently being conducted, which evaluate the effects of aspirin, sulfinpyrazone, or dipyridamole in combination with aspirin in the secondary prevention of myocardial infarction. A critical review of these trials indicates a range of evidence from no difference to a favorable trend that antiplatelet drugs may serve as anti-thrombotic agents in man. To date, a definitive answer concerning the therapeutic effects of these drugs in the secondary prevention of coronary heart disease is not available.